Gospodarka energetyczna miast w świetle koncepcji ekorozwoju - Drzazga, Dominik (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
This paper deals with the issue of complex and integrated view at the energy management in city. The background for this approach is the theory of city ecology, in contrast to the traditional, narrow one, which focus only on the supply side of energy management. In the first part, the paper presents a concept of city ecology and a relationship with city energy management. In the following part, there is a description of unsustainable, anthropogenic energy flows in city and the main directions of energy rationalisation and energy conservation in municipal sector. Next part of this paper presents the concept of integrated energy management as an approach which integrates supply and demand side of local energy market with land use management and spatial planning. The paper finish with recommendations addressed to local land use plans and local energy plans aimed at creating sustainability in energy sector in city. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1083, s. 433-441